Do workers benefit from wage transparency rules? - Oliver Gürtler; Lennart Struth (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2021)
Wage transparency rules arguably enable workers better to assess their contribution to firm value, allowing them to make wage demands that more accurately reflect their value for the employing firm and to lower wage gaps in turn. This paper contains a formal analysis of transparency rules and their effects on wages. We find that these rules induce firms to behave strategically with the aim of manipulating the information workers receive. We identify a large class of rules that yield an identical equilibrium outcome. For productivity distributions with decreasing (increasing) hazard rate, transparency rules increase (potentially decrease) workers' payoff.
Keywords: J31; J71; K31; M51; 330; Wage-setting; transparency rule; payoff; strategic effect; learning effect